Solutions for Lithium Battery Materials Data Issues in Machine Learning: Overview and Future Outlook - Pengcheng Xue; Rui Qiu; Chuchuan Peng; Zehang Peng; Kui Ding; Rui Long; Liang Ma; Qifeng Zheng (Advanced Science)
Abstract The application of machine learning (ML) techniques in the lithium battery field is relatively new and holds great potential for discovering new materials, optimizing electrochemical processes, and predicting battery life. However, the accuracy of ML predictions is strongly dependent on the underlying data, while the data of lithium battery materials faces many challenges, such as the multi‐sources, heterogeneity, high‐dimensionality, and small‐sample size. Through the systematic review of the existing literatures, several effective strategies are proposed for data processing as follows: classification and extraction, screening and exploration, dimensionality reduction and generation, modeling and evaluation, and incorporation of domain knowledge, with the aim to enhance the data quality, model reliability, and interpretability. Furthermore, other possible strategies for addressing data quality such as database management techniques and data analysis methodologies are also emphasized. At last, an outlook of ML development for data processing methods is presented. These methodologies are not only applicable to the data of lithium battery materials, but also endow important reference significance to electrocatalysis, electrochemical corrosion, high‐entropy alloys, and other fields with similar data challenges.